User's perception towards implementation of CMMS in government building / Nur Fatihah Mohd Awal - Mohd Awal, Nur Fatihah (2014)
With Information Technology (IT) nowadays, there are many things that can be developed to a new change and maintenance management also part of it. To help in maintaining the building, Computerized Maintenance Management System (CMMS) had been introduced to world. It is a computer software package that works to organize the organization's maintenance operation and it has been developed into many parts such as arrange, advance and monitor all maintenance activities. CMMS also a device that helps the department to manage the assets in computerized data based information and inventory.